Ugryź mnie! Kanibalizm jako metoda przekładu - Tapscott, Stephen (Er(r)go. Teoria - Literatura - Kultura, 2003)
Stephen Tapscott Bite me! Cannibalism and the Uses of Translation In his essay Stephen Tapscott claims that a postmodern approach to modernist texts can be described as cannibalistic. As an example of that kind of approach he cites the literary history of Latin America and its experience of colonialism as well as postcolonialism. Also, he focuses on the postcolonial discourse present in Columbus' s diaries. Then Tapscott presents the evaluation of the Shakespearean metaphor of Caliban and its reception in South America. Finally, he goes on to discuss the openly cannibalistic poetry of Pablo Neruda. He argues that Latin American postmodemism is cannibalistic in at least two ways: first. in the sense that it derives from the rich tradition of moral and political (not necessarily physical) cannibalism, and secondly, that it cannibalises the very postcolonial discourse forced on America in the times of European domination. The conclusion is that postmodemism (including the Latin American postmodemism) cannibalises the cannibalised.